(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: Coronary artery disease (CAD) can occur due to atherosclerosis in coronary arteries. Platelet agreement plays an important role in the pathophysiology of CAD. CD40L is a surface antigen on activated platelets. CD40L will bind to CD40 which is expressed by macrophages and endothelials then this activation results in reduced thickness and stability of atherosclerotic plaque and then thrombus appears. Thrombus ultimately inhibits blood flow to the coronary arteries. Proper measurement of these activities can describe the occurrence of CADs driven by platelets. Objectives: Measuring the avidity of CD40L-CD40 interactions so that the relationship between CD40L activity and CAD events can be seen. Materials and Methods: This research is non-experimental in nature and uses Case control designs. The subjects of the study were CAD patients at RSUD Dr. Soedirman Kebumen. Patients who met the inclusion and exclusion criteria were then examined and healthy patients were matched and CAD patients matched. The subject’s blood is then drawn and sent to Clinical Pathology Laboratory, Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada. Blood samples were then examined using flow cytometry to determine CD40L levels. The results obtained were then analyzed by logistic regression test with Medcalc software. Results and discussion: Twenty-six subjects participated in this study, with 13 subjects were CAD patients and 13 healthy control subjects.The percentage of platelets expressing CD62P+ CD40L+ in the CAD group was higher than in the control group (p = 0.0015). Statistical analysis with T test showed that there were significant differences in CD40-expressing platelets between the CAD group and the control group (p = 0.0029).The study conclude that the avidity of CD40L-CD40 interactions as indicated by CD40 expression is related to CAD events. CD40 expression was higher in subjects with CAD compared to controls. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.796-800